Sistem Hukum Adat Terhadap Upaya Penyelesaian Perkara Pidana - La Syarifuddin (Fakultas Hukum Universitas Mulawarman, 2019)
The concept of the state of law, fairy legal certainty is not only be reached with the arguments contained in the Law. In Indonesia, it is one country that is not only based on the law, but also sees the development of values that live in society, namely customary law. The existence of customary law in an effort to settle cases still has a place and is adopted and implemented in various communities, this process is still running today. Various types of systems for implementing dispute resolution through customary institutions to settle criminal cases are an out of court process on the wishes and the agreement which is acceptable to all parties.